Enabling of Automatically Generation of Cutting Paths for Three-Dimensional Pre-Contouring with Waterjet Trimming - Waldemar Reder; Eckart Uhlmann (Journal of Machine Engineering)
Abrasive Water Injector Jet Cutting (AWIJC) is a flexible machining process for manufacturing high-performance materials, such as titan- and nickel-base-alloys. Due to the low ductility and thermal conductivity of these materials, conventional machining is struggling with high tool costs and wear. The tool wear in AWIJC is independent of the machined material, and the process has the potential to provide a cost-efficient solution in machining high-performance materials. Trimming, a near-net-shape pre-contouring with multi-stage AWIJC, requires a detailed knowledge of cutting paths for all steps in advance. In order to enable a geometrical flexible manufacturing process, an automatically cutting path generation is necessary. This article presents an application developed with NX Open using Visual Basic. The application TrimCAD is able to provide all necessary geometries for trimming based on the geometries of initial and finished parts. TrimCAD is an innovative possibility to machine three-dimensional parts made of high-performance materials.